KETELADANAN ORANG TUA DAN GURU DALAM PERTUMBUHAN DAN PERKEMBANGAN ANAK USIA DINI - Suhono Suhono; Ferdian Utama (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2017)
This research has a background in education that the phenomenon should be addressed immediately, because there are still many as an educator has not been able to exercise his duty and many educators who deliver learning aren't competent in the field of science, so be bad for generations beyond. Example of parents and teachers make the most superior education concept in the process of growth and development of learners. The research problem is how to understand the exemplary of parents and teachers to educate the children in its relevance towards the growth and development of the child's parents and teachers Example in the growth and development of children Parenthood And Teacher In Growth and Development of Early Childhood (Perspective Abdullah Nashih Ulwan Review Book of Tarbiyyah Al-Aulad Fi Al-Islam ). The researchers used library research and used the historical and philosophical approach. In analyzing the data, researchers used “tekhnik analisis dan deskriptik analitik” The Result showed that that the concept Model of Abdullah Nashih Ulwan was influentif and it was the most convincing method of success in preparing children to improve their personality in moral, social, and spiritual. Therefore as an educator must possess a good example figure, according to the criteria of the teachings given by Islam on akhlakul karimah.